THE IMPORTANCE OF EARLY CHILDHOOD EDUCATION IN THE DIGITAL TRANSFORMATION ERA - paramitasari, ayu (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2021)
Early childhood education is an important issue to be discussed and addressed by parents and teachers as educators. As a result, the total population of 264 million people in Indonesia, there are 171.17 million people or around 64.8 percent who are already connected to the internet. This figure increased from 2017 when the internet penetration rate in Indonesia was recorded at 54.86 percent. By being given an education from an early age, children can use gadgets to find topics that match the subject matter at school, in addition to facilitating communication with parents and other family members. While digital technology can be used to help children learn and develop, it is up to parents to monitor what kind of information is accessible. Parents face many challenges in educating, raising, and nurturing their children in today's digital era.